Integration of strategic and project management at the enterprises of the transportation complex - Marunych, Valerii; Kharuta, Vitalii; Kharuta, Valentyna; Kravchuk, Serhii; Hryhorevska, Myroslava (Technology audit and production reserves, 2021)
The object of research is the integration processes of strategic and project management at the enterprises of the transport complex. The rapid pace of development of science and technology requires modern effective management tools in any sector of the economy, in particular, in the transport sector. The effective development of the transport industry is of fundamental importance both for the development of regions and for the country as a whole. This is due to the fact that the availability of transport facilities is an essential condition for the development of productive forces, a means of meeting the demand for freight and passenger transportation, ensuring the socio-economic unity of the state. There is a need for a strategic approach to the management of transport enterprises, the development of a unified approach to the integration of strategic and project management at transport enterprises as their long-term goals and objectives. Therefore, it acquires particular importance as a means of implementing the action program, which clarifies the goals and means of implementing the chosen path of development. The paper proposes the construction of a conceptual model for the integration of strategic and project management at the enterprises of the transport complex, based on the implementation of the following stages: – analysis of the stages of strategic and project management of enterprises is carried out; – process of integration of strategic and project management at the enterprises of the transport complex is being built; – on the basis of the developed integration process, a conceptual model for the integration of strategic and project management at the enterprises of the transport complex is being built. As a result of this research, a conceptual model for the integration of strategic and project management at transport enterprises was developed, which combined separate approaches to management. This result made it possible to obtain an effective tool for integrated strategic and project management of transport enterprises, which will be useful in the process of forming their development strategy.